Effectiveness of drug-loaded poly(ethylene glycol) and poly(lactic-co-glycolic-acid) nanoparticles in the in vitro treatment of breast cancer: a systematic review - Sandoval-Vásquez, Cristian; Cárcamo, Isabella; Lagos, Paula; Muñoz, Anaís; Zavala, Francisco; Colil, Valentina; Villagrán-Silva, Francisca; Vásquez-Carrasco, Edgar; Hernandez-Martinez, Jordan; Valdés-Badilla, Pablo; Torrens, Francisco; Fincheira, Paola; et al. (Frontiers in Pharmacology, 2026)
BackgroundBreast cancer treatment remains a major challenge to modern medicine and has driven the need for nanotechnology-based strategies to improve drug delivery and overcome chemoresistance. Poly(ethylene glycol) and poly (lactic-co-glycolic acid) (PEG–PLGA) nanoparticles (NPs) are a type of FDA-approved biodegradable copolymer (lactic + glycolic acids) that degrades into non-toxic metabolites (lactic acid and glycolic acid); it has emerged as a promising drug carrier owing to its biocompatibility, sustained release properties, and ability to enhance the cellular uptake of chemotherapeutic agents. This systematic review examines the efficacies of PEG–PLGA nanoparticles loaded with antineoplastic drugs on in vitro models of breast cancer cell lines.MethodsFollowing PRISMA guidelines, we conducted a comprehensive search of the Web of Science, Embase, MEDLINE, and Scopus databases to identify experimental studies published between 2014 and August 2025 that evaluated PEG–PLGA formulations applied to breast cancer cell lines. The methodological quality of each study was appraised using the National Institute for Health and Care Excellence (NICE) criteria.ResultsThirteen studies were chosen based on our inclusion criteria. Here, the PEG–PLGA nanoparticles were predominantly spherical (30–210 nm) and exhibited controlled release kinetics. Compared with free drugs, the nanoformulations significantly reduced cell viability, increased apoptosis, and induced cell-cycle arrest. Functionalization with ligands such as folic acid enhanced drug targeting and cytotoxicity, while the molecular analyses revealed upregulation of p53, Bax, and caspases as well as downregulation of Bcl-2 and hTERT genes.ConclusionPEG–PLGA nanoparticles can substantially improve the selectivity, bioavailability, and cytotoxic efficacies of anticancer drugs in breast cancer in vitro. These findings underscore their translational potential as next-generation drug-delivery systems, warranting in vivo validation as well as development of theranostic- and stimulus-responsive designs for personalized oncology.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251076570.